Glam Rock and Funk Alter-Egos, Fantasy, and the Performativity of Identities - Bradley, Monica (2017)
The following article explores different conceptions of fantasy and science ction that characterized many popular music performances in the 1970’s predominantly in the genres of glam rock and funk. By focusing on a few artists that were at the peak of their music careers at this time, such as David Bowie, P-Funk, Queen, Labelle and others, it attempts to un-earth some historical conditions for women, queers, and people of color and reveal how these artists have attempted to escape and transform certain realities by transgressing the boundaries of real/ ction, masculinity/ femininity, race, sexuality, and the “alien”. El siguiente artículo explora las diferentes concepciones de fantasía y ciencia cción que caracterizan muchas formas de actuación en la música popular de los años setentas, predominantemente en los géneros de glam rock y funk. Pondré especial atención en algunos artistas que estuvieron en el ápice de su carrera musical en este tiempo como David Bowie, P-Funk, Queen, Labelle, y otros quienes intentaron traer a la realidad temas sobre condiciones históricas en mujeres, queers y personas de color . Asimismo, demostraré la forma en que estos artistas intentaron escapar y transformar ciertas realidades mediante la trasgresión de los límites entre realidad/ cción, masculinidad/feminidad, la raza, la sexualidad y el “alien”.